A study on post intervention impact assessment of antibiotic prescribing practices in the neurosurgery ICU, under antimicrobial stewardship program - Richa Mishra; Arushi Omar; Harshit Verma; Rajesh Harsvardhan (Wolters Kluwer -Medknow Publications, 2023)
Introduction: Antimicrobial Stewardship is a coordinated program that ensures the optimal selection, dose, and duration of an antimicrobial therapy that leads to the best clinical outcome for the treatment or prevention of an infection. Objectives: Objectives of the study are, (1) to describe antibiotic stewardship program implementation by critically evaluating antibiotic prescribing practices; (2) to design an appropriate intervention for subsequent implementation; and (3) to discern the impact of intervention. Methodology: An interventional and cross-sectional study was carried out for 19 months in a neurosurgery intensive care unit (ICU) of a tertiary-care hospital, consisting of three phases: baseline, intervention, and postintervention. First phase involved the evaluation of antibiotic utilization and prescribing practices and appropriateness for the same without provision of any recommendations. In second phase, a 3-component intervention was introduced, i.e. active ICU rounds, postprescription review with feedback and teaching programs. Third phase involved evaluation of antibiotic utilization and prescribing practices and appropriateness for the same with provision of recommendations. The study tool was an antibiotic prescription chart (pre and post-intervention phase) and postprescription review and feedback form (only postintervention phase) that was used for data collection. The primary outcome of the study was days of therapy (DOT) per 1000 In-patient days (PD) for antimicrobials. Data analysis was done by SPSS 23. Results: Overall decrease in the DOT per 1000 In-patient days from baseline to postintervention phase was 17.8% (P = 0.35). The reduction in cost of antibiotic usage per patient day from preintervention phase to postintervention phase was INR 78.1. Conclusion: Antibiotic stewardship ward rounds and dedicated prescription chart can achieve reduction in antibiotic consumption.